Pengaruh Penerapan Strategi Pembelajaran Active Learning, Berpikir Kritis, Pada Masa Pandemi Terhadap Hasil Belajar Ekonomi Siswa - Aminah Rehalat; Zuhria Nurul 'Ainy (Universitas Hamzanwadi, 2022)
Study was 18 students of class VIIIA as the experimental class and 18 students of class VIIIB as the control class. The instrument used to measure student learning outcomes is a test (pretest and posttest) in the form of multiple choice , totaling 10 numbers and a questionnaire to determine the views and responses of students about the application of active learning strategi, Analysis of pretest and posttest data to examine the comparison of N-Gain values between the experimental class and the control class. The N-Gain value was 0.7810 for the experimental class and 0.3789 for the control class. Ui hypothesized the posttest data of the experimental class and the control to test the t-value, and the results obtained were T-count (7.455) T-table (2.032). So the decision taken is H0 is rejected and Ha is accepted. This shows that there is an effect of applying active learning strategies during the pandemic on economic learning outcomes for students of class VIIIA at SMP Negeri 2 Ambon foe experimental studies on economics subjects